Tourism and Real Estate Development at Coco Beach - Solano, Leyla (2011)
In the framework of the efforts of social responsibility from a real estate developer in Ocotal- playas del Coco, carried out a community diagnosis in playas del Coco, which gave information key to the determination of the areas of social investment by the company. This article focuses on the problems of the area, major found products of research findings, as well as some conclusions on the approach by the enterprise and social responsibility that should in general be enterprises linked to tourism development in real estate of playas del Coco, Carrillo, Guanacaste.